Clinical Characteristics, Treatment Patterns, and Survival Outcomes of Right-Sided RAS/RAF Wild-Type Metastatic Colorectal Cancer: A Real-World Multicenter Cohort Study - Nur Deniz Yildiz; Çağatay Arslan; İlker Nihat Okten; Umut Kefeli; Mahmut Emre Yildirim; Nuri Karadurmus; Tuba Baydas; Bülent Karabulut; Irfan Cicin; Cemil Bilir; Melike Ozcelik; Timucin Cil; et al. (Clinics and Practice, 2026)
Background: Right-sided metastatic colon cancer represents a clinically distinct subgroup with inferior outcomes and uncertain optimal biologic treatment selection, even among patients with RAS wild-type disease. Real-world data focusing specifically on right-sided RAS wild-type metastatic colon cancer remain limited. This study aimed to describe clinicopathologic characteristics, metastatic patterns, treatment approaches, and survival outcomes in this population using a national multicenter registry. Methods: This retrospective multicenter cohort study was conducted using data from the ONKO-KOLON Türkiye registry. Patients with pathologically confirmed KRAS/NRAS wild-type metastatic colorectal cancer and available primary tumor localization were evaluated. The main analytic cohort included patients with right-sided metastatic colon cancer, defined as right colon or transverse colon tumors. Left-sided colon cancer patients were used as a contextual comparator, while rectal cancer patients were excluded from sidedness-based colon comparisons. Survival outcomes were estimated using the Kaplan–Meier method, and prognostic factors were evaluated using Cox regression analyses. Results: Among 1079 patients in the source cohort, primary tumor localization was available in 1065 patients. Of these, 213 had right-sided colon cancer, 464 had left-sided colon cancer, and 388 had rectal cancer. In the right-sided cohort, median age was 61.5 years, 64.3% were male, and 66.7% had synchronous/de novo metastatic disease. Liver metastasis was the most common metastatic site (63.4%), followed by lymph node (31.0%), lung (21.1%), and peritoneal metastases (15.5%). First-line anti-VEGF-based treatment was used in 46.0% of patients, while anti-EGFR-based treatment was used in 40.8%. Among evaluable patients, the objective response rate was 46.8% and the disease control rate was 79.2%. Median progression-free survival was 10.0 months, and median overall survival was 24.0 months. In unadjusted exploratory analysis, median OS was 27.0 months with anti-EGFR-based treatment and 17.0 months with anti-VEGF-based treatment (log-rank p = 0.022), whereas median PFS was 10.0 months in both groups. In an extended covariate-adjusted multiple-imputation sensitivity model, the anti-EGFR OS estimate did not meet statistical significance (adjusted HR 0.66, 95% CI 0.43–1.00; p = 0.051). In a secondary contextual comparison, median overall survival was shorter in the right-sided than in the left-sided colon cancer group (24.0 vs. 28.0 months; HR 1.47, 95% CI 1.19–1.82; p < 0.001), whereas progression-free survival did not differ significantly. Conclusions: This study provides a descriptive account of metastatic patterns, treatment approaches, and outcomes in a dedicated right-sided RAS wild-type metastatic colon cancer cohort. The unadjusted OS difference between biological treatment groups was not confirmed after measured covariate adjustment and should not be interpreted as evidence of comparative treatment effectiveness. Because molecular profiling was incomplete, this study cannot identify biomarker-defined treatment subgroups. Prospective studies with complete, predefined molecular characterization are needed before molecularly informed treatment selection hypotheses can be evaluated in this population.